Climate Change and International Conflict: How Climate Change’s Impact on the Nile Affects Egypt-Ethiopia Conflict - Mohammad, Rafsyanjani (Journal of Islamic World and Politics, 2020)
This article aims to explain the influence of climate change on the international conflict between Egypt and Ethiopia. Climate change phenomenon was already felt in various parts of the world, but its impact will be more significant if it hits hotspot areas such as the Nile. Therefore, first, the author will describe a literature review of relations between climate change and international conflict. Second, the article will explain how the climate change phenomenon in the Nile is resulting in some security risks, especially toward Egypt. The result of this research concludes that the climate change phenomenon in the Nile can exacerbate the conflict escalation between Egypt and Ethiopia along with security threats in Egyptian water, food, and economy as the result of climate change. Although many who doubt the possibility of armed conflict, Nile’s condition as one of the hotspots areas of climate change and coupled with the absence of comprehensive international river management make all options are still counted and must be undertaken cautiously.